Effect of coconut meal inclusion in broilers diets - Bastos, Silvana (2008)
The experiment aimed to evaluate the effects of coconut meal inclusion (CM) in diets over the performance and carcass traits of commercial broilers. 576 male birds from a commercial line with seven days of age were distributed in a completely randomized design with six treatments and eight replicates of 12 birds each. Treatments consisted of six isonutrientes diets containing 0; 3.5; 7.0; 10.5; 14.0 e 17.5% of CM. As soon as the level of the food increased, there was a liner reduction on feed intake (FI) and weight gain (WG) in all periods. For food conversion (FC) there was a quadratic effect on the initial and linear on the total period. In relation to the control group it was observed that the birds fed with ration containing CM reduced the consumption and the weight gain as well as they had the worst food conversion. On the final period the consumption and weight gain were not different among the treatments. Carcass characteristics were not affected by CM inclusion. We concluded that coconut meal inclusion must be 5% on 7 to 21 days of age and 17.5% on 21 to 42 days of age, respectively.